Dampak Program Keluarga Harapan Terhadap Kesejahteraan Keluarga Di Kelurahan Mayangan Kota Probolinggo - Nurdiana Holida; Martina Eka Saputri; Icha Cahya Kusuma Ningtias (Institut Nalanda, 2023)
The Family Hope Program or PKH is a conditional cash assistance program that is given to families who have very low incomes. What is needed is involvement in pursuing education and health. PKH in Indonesia was founded in 2007, to reduce poverty and improve low family welfare. This study aims to determine the impact of PKH on family welfare in the Mayangan Village, Probolinggo City. With this type of qualitative research and descriptive qualitative approach. Observations, interviews, and documentation are data collection techniques used in this writing. To test the credibility of the data or trust in the data, namely using the triangulation method and increasing the persistence and adequacy of references. The results of this study indicate that there is an impact of PKH on increasing family welfare in the Mayangan Village, Probolinggo City, namely there are two positive and negative impacts. From the positive impacts obtained, namely, reducing the burden of spending, increasing children's education, improving family health, changing behavior and independence of poor PKH recipient families. Meanwhile, the negative impact arises from the implementation of the Harpan family program in the Mayangan Village, Probolinggo City, namely dependence on assistance provided by the government. In addition, it also creates social jealousy among local residents who do not receive PKH assistance.